Development of chitosan scaffolds functionalized with bioactive oxides for dentin tissue engineering - Melo, Camila Correa da Silva Braga de (2025)
The regeneration of the dentinpulp complex represents one of the major challenges in restorative and regenerative dentistry, requiring the development of biomaterials capable of promoting appropriate cellular responses and mineralized matrix formation. In this thesis, bioactive chitosan-based scaffolds functionalized with inorganic oxides were developed and characterized for potential applications in dentin tissue engineering and conservative pulp therapies. In the first study, chitosan scaffolds containing different concentrations (0.0250.1% v/v) of magnesium oxide (MgO) or silicon dioxide (SiO) were produced by phase separation and lyophilization and characterized in terms of their physicochemical and biological properties. The analyses revealed an organized porous network, high hydrophilicity, controlled degradation rate, and sustained oxide release. Dental pulp cell assays demonstrated that the scaffolds were biocompatible and supported cell viability, proliferation, and differentiation, with MgO-containing formulations showing enhanced proliferative activity and increased expression of odontogenic markers. In the second study, calcium-containing chitosan scaffolds were incorporated with MgO at different concentrations (0.0250.1% v/v) and evaluated for porosity, degradation, ionic release, and biological performance. The presence of calcium increased porosity, while MgO modulated pore architecture without compromising biocompatibility. Formulations containing 0.1% MgO promoted higher cell proliferation and mineralized matrix deposition, indicating a synergistic effect between calcium and MgO. Overall, the results demonstrate that functionalization of chitosan with bioactive compoundsparticularly MgO and calciumenhances the physicochemical properties and bioactivity of the scaffolds, promoting odontogenic differentiation and mineralized matrix deposition. These findings highlight the potential of such biomaterials as promising bioactive platforms for dentin regeneration and pulp vitality maintenance in conservative therapies.